Farmacovigilância na terapêutica específica de Leishmaniose visceral em hospital de referência de Belém do Pará - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Pará, 2011)
Retrospective descriptive and analytical, systematic analysis of the records of patients admitted to the hospital of infectious and parasitic diseases with the diagnosis of visceral leishmaniasis between the years 2004 to 2009, analyzing the clinical, therapeutic and laboratory features of 348 patients with objective to determine the occurrence and frequency of adverse drug reactions (ADR) used in the specific therapy. The indication of meglumine antimoniate (GNM) was the predominant drug of first choice in 318 patients (91.38%), and the mean treatment of 18.6 days (SD ± 1.95) and the average concentration of 611mg/dose ( SD ± 294.4) while the second choice of therapy with amphotericin B deoxycholate (ABDC), we identified a mean of 22.67 days (SD ± 8.14) and average concentration of 24.33 mg / dose (± 13 , 79). We identified the occurrence of ADR 342 in 184 patients (52%), and Type A reactions (N = 337/98, 54%) were predominant and algorithms Karch & Lasagna, provided better sensitivity for determination of causality of ADR. Patients using GMN had 291 responses (85.09%), and the frequent occurrence of hyperthermia (N = 109) in patients aged 5 years or less. Pancreatitis drug was identified on two occasions and classified as serious and identified six cases of elevated transaminase levels after instituting the use of GML and one after therapy with ABDC, as drug-induced hepatitis. Approximately 9.28% of ADR associated with the use of GML, were related to cardiovascular changes. The occurrence of hypokalemia in twelve patients was associated with the ADR frequent use of ABDC. There is need to establish routine monitoring of hospital performance ADR to anti-leishmanial and prospective studies from the results shown in order to evaluate the dose-response relationship for the occurrence of preventable ADR.
Keywords: Leishmaniose visceral; Reações adversas a medicamentos; Visceral leishmaniasis; Adverse drug reactions; Doenças infecto-parasitárias; Medicamentos - Efeitos colaterias; Terapêutica - Complicações e sequelas; CIÊNCIAS DA SAÚDE